Family Library as a Site of Memory: the Rozumovskys’ / Razumovskys’ Book Collection from the Mid-Eighteenth to the Early Twenty-First Century - Svitlana Potapenko (Kyiv-Mohyla Humanities Journal)
This article focuses on the book collection whose history began in the mid-eighteenth century and despite certain losses continues nowadays 1 . This is a sole known book gathering that belonged to the Ukrainian ruling dynasty and still finds itself in the possession of the family. The Counts Razumovsky, who trace their ancestry from the hetman Kyrylo Rozumovsky (1728– 1803), held first-class libraries in their Ukrainian, Russian, Austrian, and Czech estates during almost three centuries. However, it is only the Viennese collection that survived the tough twentieth century and sheds light on the bookish tastes of its aristocratic proprietors. At the same time, the catalogues of 1907 and 1914 reveal the repertoire of the lost assemblages, offering a broader exploration of the family book tradition possible. The theoretical frame of the lecture refers to the contemporary memory studies with a special attention to family memory.